High-performance flexible quasi-solid-state zinc-ion batteries with layer-expanded vanadium oxide cathode and zinc/stainless steel mesh composite anode. (August 2019) - Zhao, Jin; Ren, Hao; Liang, Qinghua; Yuan, Du; Xi, Shibo; Wu, Chen; Manalastas, William; Ma, Jianmin; Fang, Wei; Zheng, Yun; Du, Cheng-Feng; Srinivasan, Madhavi; et al.
Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) featured with environmental friendliness, low cost, and high safety have attracted great interest but still suffer from the lack of high-performance electrodes. Herein, a facile in situ approach is developed to simultaneously introduce multivalence, increase the interlayer water content, and expand the interlayer distance in hydrated V2 O5 . These structural modulations endow the as-obtained layer-expanded V2 O5 2.2H2 O (E-VO) nanosheets with faster charge transfer kinetics, more Zn 2+ storage space, and higher structural stability than precursor V2 O5 . Besides, a unique flexible Zn/stainless steel (Zn/SS) mesh composite anode with low polarization and uniform Zn stripping/plating behavior is fabricated, which alleviates the Zn dendrite growth. As cathode for aqueous ZIBs, E-VO exhibits high reversible capacity (450 mAh g −1 at 0.1 A g −1 ), good rate capability (222 mAh g −1 at 10 A g −1 ) and long stability (72% capacity retention for 3000 cycles at 5 A g −1 ). Moreover, the flexibility and large lateral size make E-VO a high-performance binder-free cathode for flexible quasi-solid-state Zn/E-VO battery, i.e. high capacity under different bending states (361 mAh g −1 at 0.1 A g −1 ), good rate capability (115 mAh g −1 at 2 A g −1 ), and long stability (85% capacity retention for 300 cycles at 1 A g −1 ). The achievements of this study can be considered as an important step toward the development of aqueous-based ZIBs. Graphical abstract: Image 1 Highlights: Hydrated V2 O5 with expanded interlayers is prepared by a facile in situ approach. Zn/stainless steel mesh composite is designed to alleviate the Zn dendrite growth. Modified V2 O5 shows much improved Zn 2+ storage capability than precursor V2 O5 . Flexible quasi-solid-state Zn-ion battery is fabricated with superb performance.